2005
DOI: 10.1002/nme.1449
|View full text |Cite
|
Sign up to set email alerts
|

State‐space time integration with energy control and fourth‐order accuracy for linear dynamic systems

Abstract: SUMMARYA fourth-order accurate time integration algorithm with exact energy conservation for linear structural dynamics is presented. It is derived by integrating the phase-space representation and evaluating the resulting displacement and velocity integrals via integration by parts, substituting the time derivatives from the original differential equations. The resulting algorithm has an exact energy equation, in which the change of energy is equal to the work of the external forces minus a quadratic form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…It is actually found that the DE 3 scheme is very similar to the one proposed by Krenk [9], which was derived from the equation of motion via a weak formulation. A significant difference between the DE 3 scheme and that proposed by Krenk concerns the handling of the contributions of the damping and the external forcing terms, which allow the DE 3 scheme to retain its fourth-(and third-) order accuracy in the conservative (resp.…”
Section: The De 3 Schemesupporting
confidence: 52%
“…It is actually found that the DE 3 scheme is very similar to the one proposed by Krenk [9], which was derived from the equation of motion via a weak formulation. A significant difference between the DE 3 scheme and that proposed by Krenk concerns the handling of the contributions of the damping and the external forcing terms, which allow the DE 3 scheme to retain its fourth-(and third-) order accuracy in the conservative (resp.…”
Section: The De 3 Schemesupporting
confidence: 52%
“…In this formula the stiffness matrix at the mean displacement can be replaced by the mean value of the stiffness matrix to within second order as shown in (18), and the displacement difference can similarly be expressed to second order by (23), resulting in the fourth-order relation…”
Section: Internal Point Formulamentioning
confidence: 99%
“…Essentially, the conservative algorithms correspond to an integrated form of the original state-space differential equations, and the order of accuracy depends on the order to which the corresponding integrals are represented in the discrete algorithm. It was demonstrated by Krenk [18] that a fourth-order algorithm could be obtained for linear dynamic systems by evaluating the integrals over the time step via integration by parts. This procedure introduces the time derivatives of the state-space variables under the integral sign, and these time derivatives can then be expressed via the original state-space equations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations